La Iglesia católica ante la sublevación militar de 1936. La provincia de León - Rodríguez González, José Javier (Estudios humanísticos. Geografía, historia y arte, 1994)
The text analyses the position of the Catholic Church in the province of León, within a frame of national and international action. This action was carried out by the ecclesiastic institution during the spanish civil war. The Catholic Church gave some theorical bases which legitimized the rebel size from the very first moment and also justified the war, so the Catholic Church participated in the fighting.